Amodiaquine failure associated with erythrocytic glutathione in Plasmodium falciparum malaria (2007)
ABSTRACT: Objective: To establish the relationship between production of glutathione and the therapeutic response to amodiaquine (AQ) monotherapy in Plasmodium falciparum non-complicated malaria patients. Methodology: Therapeutic response to AQ was evaluated in 32 patients with falciparum malaria in two townships of Antioquia, Colombia, and followed-up for 28 days. For every patient, total glutathione and enzymatic activity (glutathione reductase, GR, and γ-glutamylcysteine synthetase, γ- GCS) were determined in parasitized erythrocytes, non-infected erythrocytes and free parasites, on the starting day (day zero, before ingestion of AQ) and on the day of failure (in case of occurrence). Results: There was found an AQ failure of 31.25%. Independent of the therapeutic response, on the starting day and on the day of failure, lower total glutathione concentration and higher GR activities in parasitized erythrocytes were found, compared with non-infected erythrocytes (p < 0.003). In addition, only on the day of failure, γ-GCS activity of parasitized erythrocytes was higher, compared with that of healthy erythrocytes (p = 0.01). Parasitized and non-parasitized erythrocytes in therapeutic failure patients (TF) had higher total glutathione on the starting day compared with those of adequate clinical response (ACR) (p < 0.02). Parasitized erythrocytes of TF patients showed lower total glutathione on the failure day, compared with starting day (p = 0.017). No differences was seen in the GR and γ-GCS activities by compartment, neither between the two therapeutic response groups nor between the two treatment days. Conclusion: This study is a first approach to explaining P. falciparum therapeutic failure in humans through differences in glutathione metabolism in TF and ACR patients. These results suggest a role for glutathione in the therapeutic failure to antimalarials.